Layering of Life (Sara novel of Peter Saric) - Kostić, Dragomir J. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Novel Sara of Petar Saric consists of two parts; in it are processed or present two wars, two major wars in the region of Montenegro and Herzegovina, the First and Second World War. However, it is more novel about divisions within the family and the man himself, (and infamous assault of godfather Luka on Sarah also and his murder are in that function), in the first part; and on the divisions among the people, in general, in the second part of the novel. The second part is, in fact, the image layering of life, not a symbolic one, full of hope, faith, reliance, rather than a concrete, real life, that life which is transformed into a fear of life. Separate, poetical, part of the novel, is his main character, Sara. It is no coincidence that her name novel entitled. Because she is one of most beautiful characters in the newer Serbian prose. Speech about the Sara precedes speech about her book. The book is Sara, Sara's book! Possession of book is her main feature of the exterior. Sara comes out from the Book and disappears in the book. Self contained and independent, therefore doomed to conflict with the environment. Loyal to husband and family, loyal to the truth and for justice, she ,,not hurt anything and anyone, no one is standing in the way, to anyone not wroth, nor has anyone looked wrong." At the same time, the strange beauty, beauty that could not fit into some sort of scheme, one particular image or idea of ​​beauty that again and again renewed, changed, remaining distant, and unmet. Strange goodness, marvelous beauty, she suffered unusual way; her life was transformed into continuous abstinence, repression, in anxiety and fear. In a word: in martirizam! Finally, in order to safeguard children, sacrificed herself. Novel is a strong critique of society which is not able to recognize the beauty / goodness!
Keywords: Book; Sara; good; evil; war; house; division; Petar Sarić